Fluid intake among university students in Jakarta - Luciana Budiati Sutanto; Prillyta Gladys Sutanto; Gracia JMT Winaktu; Helena Fabiani (Indonesian Nutrition Association, 2023)
The significance of fluid intake cannot be underestimated, as it plays a vital role in regulating body temperature and enhancing cognitive function, especially in individuals experiencing thirst, while maintaining concentration. Fluid intake can be derived from various sources such as food, beverages, and metabolic processes. The objective of this study was to investigate the fluid intake among university students in Jakarta.